Perbedaan Kecenderungan Somatisasi Antara Mahasiswa Semester IV yang Memiliki Tingkat Kecemasan Tinggi dan Rendah di Fakultas Kedokteran Universitas Sebelas Maret Surakarta - . Arifa; Djoko Suwito; Diffah Hanim (Nexus Kedokteran Klinik, 2014)
Background: Somatization disorder is the presence of somatic complaints (physic) which can not be found the adequate medical explanation. Anxiety is a feeling disorder which characterized by a feeling of fear or concern that deep and sustained. Anxiety can occur in the fourth semester students. This research aims to find out is there any difference of the somatization tendencies between semester IV students who have high and low levels of anxiety in Medical Faculty of Sebelas Maret University Surakarta. Methods: This was an analytic observational research with case-control design. The subject were fourth semester students in Medical Faculty of Sebelas Maret University who meet established criteria. The sampling technique using total sampling of a large population of 237 people. The data analysed by using SPSS for Windows version 17.0 programme with the normality test by Shapiro-Wilk continued by Mann-Whitney because the data that taken was not normal distribution. Results: Students with high anxiety level was obtained an average IRS score of 15.75 and SD 6.883. Students with low anxiety level was obtained an average IRS score of 5.33 and SD 3.467. The difference of somatization tendencies between semester IV students who had high and low levels of anxiety generate significant value (p = 0.000) Conclusions: There were difference of somatization tendencies which statistically significant betweet semester IV students who had high and low levels of anxiety. Students who had high level of anxiety are more likely to experience somatization compared to students who had low level of anxiety. Keywords: Level of anxiety, somatization tendencies, medical students.